2022
DOI: 10.1002/joc.7554
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of atmospheric vapour transport and their connection to drought in New Zealand

Abstract: The impacts of drought can be substantial, particularly for primary producing nations such as New Zealand. Despite the importance of drought, identifying connections to atmospheric drivers remains a challenge. Vertically integrated water vapour transport (IVT) is critical to understanding the connection between ocean, atmosphere and the land surface, and as such the drivers of drought events. Self‐organizing maps (SOMs) are used here to characterize the spatial patterns of IVT over New Zealand. In turn, the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
4
3
0
Order By: Relevance
“…The case study of ANZ can also be used to discuss the detection criteria for ARs, and especially the role of meridional transport of moisture and heat. ARs landfalling in the northern parts of ANZ are in very good agreement with the typical image one can have of ARs landfalling in the southern mid‐latitudes (Bennet & Kingston, 2022; Kingston et al., 2022; Prince et al., 2021a), that is, a connection linking the (sub)tropical latitude to the extra‐tropics, probable moisture sources located over the Coral and Tasman Seas east of Australia, and larger occurrence during the austral summer season. By contrast, in the southern regions of ANZ, placed under the direct influence of the dominant mid‐latitude westerly winds, detected AR events are more zonal, and show limited connection with the lower latitudes—a matter also discussed more generally by Guo et al.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The case study of ANZ can also be used to discuss the detection criteria for ARs, and especially the role of meridional transport of moisture and heat. ARs landfalling in the northern parts of ANZ are in very good agreement with the typical image one can have of ARs landfalling in the southern mid‐latitudes (Bennet & Kingston, 2022; Kingston et al., 2022; Prince et al., 2021a), that is, a connection linking the (sub)tropical latitude to the extra‐tropics, probable moisture sources located over the Coral and Tasman Seas east of Australia, and larger occurrence during the austral summer season. By contrast, in the southern regions of ANZ, placed under the direct influence of the dominant mid‐latitude westerly winds, detected AR events are more zonal, and show limited connection with the lower latitudes—a matter also discussed more generally by Guo et al.…”
Section: Discussionsupporting
confidence: 85%
“…These results are verified for the northern regions of ANZ, they still hold for the West Coast of the South Island, but air humidity from the subtropics seems of little importance for the southernmost parts of the country (Figure S13 in Supporting Information ). The different moisture sources, from higher latitudes, that could affect this part of the country, corroborate the results of Bennet and Kingston (2022) on the spatial patterns of IVT in ANZ, and are also coherent with Reid et al. (2022) who obtained similar results for Australia.…”
Section: Ar and Wt Inter‐relationshipssupporting
confidence: 89%
“…For New Zealand, the role of land-atmosphere coupling is poorly understood, with no countrywide study yet performed, despite continued research into drought, heat wave and extreme precipitation events across the country (e.g. Bennet and Kingston, 2022;Reid et al, 2021;Salinger et al, 2019). For example, Salinger et al (2019) identified high temperatures across New Zealand during the 2017/2018 summer which were coupled to sea surface temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…New Zealand is exposed to extreme hydrometeorological events, including droughts (Bennet & Kingston, 2022), heat waves (Harrington, 2021;Salinger et al (2019)) and extreme precipitation (Reid et al, 2021), which are likely to be exacerbated under a changing climate (IPCC, 2021). However, the role that land-atmosphere coupling plays in the development and magnitude of these events remains unexplored.…”
mentioning
confidence: 99%